Taxonomy, Bionomics and Faunistics of the Nominate Subgenus of Mylabris Fabricius, 1775, with the description of five new species (Coleoptera: Meloidae: Mylabrini) - Pan, Zhao; Bologna, Marco A. (Zootaxa, 2014)
The nominate subgenus of the mylabrine genus Mylabris is revised: five new species, M. (M.) alpicola sp.n., M. (M.) cernyi sp.n., M. (M.) mediorientalis sp.n., and M. (M.) pseudoemiliae sp.n., are described and figured; M. (M.) apiceguttata sp.n., is provisionally refered to the nominate subgenus. M. (M.) rishwani Makhan, 2012 is synonymized with M. (M.) quadripunctata (Linnaeus, 1767). The other 20 species are characterized by short descriptions and figures, and a key to the species is provided. Tentatively, M. barezensis  and M. batnensis are placed in the nominate subgenus. The bionomics of the species is summarized in tables including information on phenology, elevation, habitat preference, host plants, larval biology, and host insects. Zoogeographic analysis of the subgenus was carried out on the basis of all available faunistic records from literature and collections which are summarized in Appendix.